Anthropologies of revolution : forging time, people, and worlds - Cherstich, Igor, 1980-; Holbraad, Martin; Tassi, Nico (University of California Press, 2020)
"What can anthropological thinking contribute to the study of revolutions? The first book-length attempt to develop an anthropological approach to revolutions, Anthropologies of Revolution proposes that revolutions should be seen as concerted attempts to radically reconstitute the worlds people inhabit. Viewing revolutions as all-embracing, world-creating projects, the authors ask readers to move beyond the idea of revolutions as acts of violent political rupture, and instead view them as processes of societal transformation that penetrate deeply into the fabric of people's lives, unfolding and refolding the coordinates of human existence"--